PEMANFAATAN LIMBAH AMPAS TEBU (BAGASSE) UNTUK PRODUKSI BIOETANOL MELALUI PROSES SAKARIFIKASI DAN FERMENTASI SERENTAK - Rigandita Ekawati, Candra Daty Novitasari, Astri Ani (Pelita - Jurnal Penelitian Mahasiswa UNY, 2015)
The aim of this research is to describe the process of bio ethanol production from bagasse with simultaneous sacharification and fermentation. The subject of this research was bagasse. The object of research was the amount of bio ethanol from fermentation of bagasse using Sacharomyces cerevisiae. The independent variable in this research was the concentration of yeast in the fermentation. There were 0.4%; 0.6%; and 0.8% of solution weight. The chemistry analysis in the research was a quantitative and qualitative analysis of ethanol using Micro Conway Diffusion and spectronic 20. The results showed the yeast concentration of 0.4% by weight solution of the hydrolysis, ethanol result was 24.555%. In the yeast concentration of 0.6% by weight of hydrolysis solution, the ethanol content was 39.571%. In the yeast concentration of 0.8% by weight of hydrolysis solution, 35.005% of ethanol was obtained. It was the highest level of ethanol on yeast concentration of 0.6% by weight solution of the hydrolysis. Keywords: bagasse, bio ethanol, fermentation, yeast, sacharification